Mortality and economic expenses of cardiovascular diseases caused by physical inactivity in Spain - Sánchez-Oliver, Antonio Jesús; García, Christian Martín; Gálvez Ruiz, Pablo; González-Jurado, José Antonio (Journal of Physical Education and Sport, 2019)
Non-communicable diseases caused 16 million early deaths in 2016 according to the data published by the World Heatlh Organization. Insufficient physical activity has become an international concern since several years ago and it is strongly related to these early deaths. The present study estimated the mortality and economic expenses of cardiovascular diseases caused by physical inactivity in Spain. Mortality attributable to physical inactivity (MA) was evaluated as the product between the population attributable fraction (PAF) and the number of deaths caused by associated cardiovascular diseases. The statistical value of life (SVL) was determined, following the human capital approach, from which SVL was estimated through the productivity lost by early death. The economic expenses were calculated using MA and SVL, classifying by gender, age group and level of physical activity. A sensitivity analysis was carried out to evaluate how the expenses vary in three possible scenarios. MA is very different regarding age and sex, with maximum levels in men between 35 and 69 years. The early death of younger individuals is more expensive, with a much lower SVL in old adults. The economic cost is much higher in the sample group with low physical activity, with an increase from 35 years and maximum values at 55-59 years. The economic costs varied, with 0.31% of the GDP for the minimum scenario, 0.09% for the medium scenario, and 0.03% for the maximum scenario. It is recommended to reinforce the development of public policies aimed at reducing sedentarism and physical inactivity in Spain
Keywords: physical activity; attitude; motivation; institutionalised elderly; Scopus